Vibriocidal Activity of Ethanol Extract of Moringa Leaves and Its Effect on the Growth of Pacific White Shrimp - Kenconojati, Hapsari; Ulkhaq, Mohammad Faizal; Azhar, Muhammad Hanif; Rukmana, Nina Rofi (Jurnal Medik Veteriner, 2023)
This study aimed to evaluate the vibriocidal potency of Moringa leaf ethanol extract (MLEE) and assess the effectiveness of dietary supplementation of MLEE on Pacific white shrimp growth performance. A vibriocidal activity was performed using disk diffusion and tube dilution methods. The results showed Vibrio parahaemolyticus was more susceptible than Vibrio harveyii with an inhibitory zone of 11.30 to 22.90 mm. The minimum inhibitory concentration (MIC) of MLEE against V. parahaemolyticus was recorded at 12.5%, similar to V. harveyii. The effectiveness of MLEE on diet was monitored by the growth of the shrimps for 40 days of culture. Shrimps with an average initial weight of 2.50±0.05 g were acclimatized in 10 days. The MLEE was administered to the shrimps at different concentrations i.e., 10%, 15%, 20%, and 25%. The control diet was prepared without MLEE supplementation. After 40 days of culture, the shrimps fed with 10% of MLEE had the best growth. This study reported that MLEE potentially become vibriocidal agents. However, the administration on shrimp had no beneficial effect on its growth performance.